Answer: Yes, the point (3,-9) is a solution to f(x) = -3x
=========================================================
Step-by-step explanation:
Since y = f(x), we can say that f(x) = -3x is the same as y = -3x
The point (3,-9) means x = 3 and y = -9 pair up together
Lets plug these values into the equation
y = -3x
y = -3(3) .... replace x with 3
-9 = -3(3) .... replace y with -9
-9 = -9
We get the same thing on both sides, so the point (x,y) = (3,-9) is a solution to y = -3x. Consequently, it's also a solution to f(x) = -3x.